2011
DOI: 10.1186/1743-422x-8-63
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive detection of the group A Rotavirus using Apolipoprotein H-coated ELISA plates compared to quantitative real-time PCR

Abstract: BackgroundThe principle of a capture ELISA is binding of specific capture antibodies (polyclonal or monoclonal) to the surface of a suitable 96 well plate. These immobilized antibodies are capable of specifically binding a virus present in a clinical sample. Subsequently, the captured virus is detected using a specific detection antibody. The drawback of this method is that a capture ELISA can only function for a single virus captured by the primary antibody. Human Apolipoprotein H (ApoH) or β2-glycoprotein 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
(23 reference statements)
1
21
1
Order By: Relevance
“…The majority of human infections are caused by viruses in group A, which can further be differentiated into 23G-and 32P-type, respectively, by VP7 and VP4 antigens [4,5]. Knowledge of the distribution of G and P genotypes, including detection of emerging genotypes, is crucial to rotavirus vaccination programmes [6].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of human infections are caused by viruses in group A, which can further be differentiated into 23G-and 32P-type, respectively, by VP7 and VP4 antigens [4,5]. Knowledge of the distribution of G and P genotypes, including detection of emerging genotypes, is crucial to rotavirus vaccination programmes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most previously published RNA detection assays for RVA required a denaturation step prior to RNA addition to the RT or RT-PCR mixture (13,14,17,28,29,(31)(32)(33)35). Typically, RVA dsRNA and oligonucleotides are mixed in a reaction vessel and heated for 5 min at 95 to 97°C followed by 1 min incubation on ice.…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR assays offer several advantages over traditional RT-PCR, including increased sensitivity, higher throughput, and faster turnaround time as well as quantification of viral loads. Several qRT-PCR assays have been developed for detection of RVA targeting VP2 (28),VP4 (29,30), VP6 (17,19,(31)(32)(33), VP7 (18,30), NSP3 (13)(14)(15)(16)34), and NSP4 (35) genes. Due to the genetic diversity of VP4 and VP6 gene segments, the NSP3 gene, encoded by genomic segment 7, has been shown to be the best target for detection of a wide variety of RVA genotypes (13-16, 34, 36).…”
mentioning
confidence: 99%
“…More recently, within the European USDEP project (www.usdep.eu), it has been shown that ApoH capture viruses including Hantavirus in both serum and urine from infected patients (Godoy et al, 2009), and very interestingly avoiding false negative generated by conventional and standard PCR methods (Fig. 10) and from stools rotavirus-infected patients permitting a very highly immune detection as sensitive as quantitative PCR (Adlhoch et al, 2011). Within the same project, many other viruses have been shown strongly bind to ApoH, including poxvirus virus, hepatitis C virus, pseudorabies virus, vesicular stomatitis virus, and Altogether these data clearly demonstrate that ApoH binds enveloped or non-enveloped DNA or RNA virus with high affinity permitting their ultrasensitive detection.…”
Section: The Use Of Apoh For Drastic Improvement Of Viral Detectionmentioning
confidence: 99%